Fear of Death between Nursing Students in the Academic and Professional Programs - Purimahua, Dora Irene; Manik, Marisa; Manurung, Evanny Indah (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND OF THE STUDY:. Nurses inevitably witness death in their professional practice. These experiences can trigger fear of a patient’s death, fear of their own death or fear of the dying process. A review of literature revealed the absence of studies on dying and feelings towards the dying process particularly fear of death among students in the Indonesian context. AIM OF THE STUDY: This study explored the levels of fear of death and the differences between students enrolled sophomore academic program and those in the professional program. METHODOLOGY: This was a quantitative comparative study that utilized a cross-sectional design. Collett-Lester Fear of Death Scale was adapted to measure the fear of death among the respondents by using univariate analysis. Bivariate analysis was also utilized by applying the independent T-test to determine the significance of the difference in the data results. All 50 professional students were included in the study while simple random sampling was done to select 50 students enrolled in the academic program. RESULTS: The level of fear of death among the sophomore students was moderate to high, while those in the professional program was moderate. Furthermore, the T-test revealed a p-value of 0.010 indicating a significant difference in the level of fear of death among sophomore academic program students compared to students in the professional program. CONCLUSION: There is a significant difference in the level of fear of death between sophomore nursing students in the academic program compared to those in the professional nursing program.